(untitled) (New Delhi, 1982)
King Akbar was very fond of Birbal. This made a certain courtier very jealous. Now this courtier always wanted to be chief minister, but this was not possible as Birbal filled that position. One day Akbar praised Birbal in front of the courtier. This made the courtier very angry and he said that the king
Keywords: Folk literature,Children's stories,Văn học dân gian,Chuyện của trẻ em; India,Ấn Độ